2022
DOI: 10.21203/rs.3.rs-2078300/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic hypoparathyroidism is associated with increased cortical bone density evaluated by high-resolution peripheral quantitative computed tomography

Abstract: Purpose This cross-sectional study aimed to evaluate BMD, bone microarchitecture and prevalent fractures in women with chronic hypoparathyroidism (HypoPT). Methods Twenty-seven women with HypoPT and 44 age-matched healthy women were included. Dual-energy x-rays absorptiometry (DXA) was used to evaluate areal BMD (aBMD) at the spine and hip as well as morphometric vertebral fractures (VFA). Microarchitecture and volumetric BMD (vBMD) were evaluated at distal radius and tibia using high resolution peripheral q… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Although our data did not show statistically different changes in BMD between both groups, a lower risk of incident fracture in patients with hypoparathyroidism compared to subjects with normal calcium metabolism was found. This finding is in line with a recent study that have shown that prevalence of fragility fractures was low in women with hypoparathyroidism and compatible with low fracture risk estimated by the FRAX tool (39). Taken together, these data suggest, although they do not demonstrate, that hypoparathyroidism protects against fracture risk (32).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although our data did not show statistically different changes in BMD between both groups, a lower risk of incident fracture in patients with hypoparathyroidism compared to subjects with normal calcium metabolism was found. This finding is in line with a recent study that have shown that prevalence of fragility fractures was low in women with hypoparathyroidism and compatible with low fracture risk estimated by the FRAX tool (39). Taken together, these data suggest, although they do not demonstrate, that hypoparathyroidism protects against fracture risk (32).…”
Section: Discussionsupporting
confidence: 90%
“…The group NH consisted of 669 patients (568 women, 84.9%) aged between 18 and 79 years (median 47 [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] years). Demographic and clinical characteristics are shown in Table 1.…”
Section: Studied Patientsmentioning
confidence: 99%
“…HypoPTH subjects compared with age-matched healthy controls are known to have lower bone turnover [C-terminal telopeptide of type I collagen (CTX), bone-specific alkaline phosphatase, osteocalcin, N-terminal propeptide of type I procollagen (P1NP)], higher areal bone mineral density (aBMD) measured via Dual-energy X-ray absorptiometry at all sites [3], with increasing aBMD with longitudinal follow-up compared with expected age-related bone loss in controls. Volumetric BMD measured via high-resolution peripheral quantitative computed tomography (hrpQCT) at the distal radius and tibia in 27 hypoPTH women and 44 age-matched healthy women noted higher cortical volumetric BMD in both radius (913 vs. 872 mg HA/cm 3 , P ¼ 0.02) and tibia (922 vs. 868 mg HA/cm 3 , P ¼ 0.001) [25]. Trabecular volumetric BMD, trabecular number, trabecular thickness and trabecular bone score were not different, suggestive that PTH has a more potent effect or cortical bone compared with trabecular bone.…”
Section: Skeletal Complicationmentioning
confidence: 99%